Bacteriological, cytological, and molecular investigation of Corynebacterium pseudotuberculosis, mycobacteria, and other bacteria in caseous lymphadenitis and healthy lymph nodes of slaughtered sheep - de Oliveira Zamprogna, Thiago [UNESP]; Ribeiro, Dayana; Azevedo, Vasco A.C.; Lara, Gustavo Henrique Batista [UNESP]; Motta, Rodrigo Garcia [UNESP]; da Silva, Rodrigo Costa; Siqueira, Amanda Keller [UNESP]; de Nardi Júnior, Geraldo; Listoni, Fernando José Paganini [UNESP]; de Souza Araújo Martins, Lorrayne [UNESP]; da Silva, Aristeu Vieira; Portilho, Fábio Vinícius Ramos [UNESP]; et al. (Springer Nature, 2021)
Caseous lymphadenitis (CL) in sheep is a chronic contagious disease caused by Corynebacterium pseudotuberculosis, commonly characterized by abscess formation in peripheral lymph nodes and disseminated infections. Nonetheless, other microorganisms, including with zoonotic relevance, can be isolated from CL-resembling lymph nodes. Currently, mycobacteria have been reported in visceral granulomatous lesions in small ruminants, a fact that poses a public health issue, particularly in slaughtered sheep intended for human consumption. Cytology using fine needle aspiration and microbiological culturing are suitable tests for routine diagnostic, whereas present drawbacks and molecular methods have been confirmatory. Data about the occurrence of mycobacteria in both lymph nodes with aspect of CL and apparently healthy visceral nodes of sheep slaughtered for human consumption are scarce. In this study, 197 visceral lymph nodes of sheep showed lymphadenitis and 202 healthy visceral lymph nodes of slaughtered sheep intended for human consumption were submitted to conventional bacteriological diagnosis, mycobacteria culturing, and cytological evaluation. Compatible Corynebacterium isolates were subjected to multiplex PCR targeting 16S rRNA, rpoB, and pld genes to detect C. pseudotuberculosis. Based on microbiological identification, C. pseudotuberculosis (86/197; 43.7%), streptococci γ-hemolytic (17/197; 8.6%), and Trueperella pyogenes (12/197; 6.1%) were prevalent in lymph nodes with abscesses, as opposed to staphylococci (53/202; 26.2%) in apparently healthy lymph nodes. No mycobacteria were isolated. Cytology identified 49.2% (97/197) Gram-positive pleomorphic organisms (coryneform aspect). Multiplex PCR confirmed genetic material of C. pseudotuberculosis in 74.4% (64/86) of the samples with C. pseudotuberculosis isolation and 66% (64/97) samples with cytological coryneform aspect (κ = 86.78%; 95% CI = 79.87–93.68%). These findings emphasize the prevalence of C. pseudotuberculosis in abscess formation among peripheral lymph nodes of sheep. Other bacteria were also identified in lymph nodes sampled that resembling C. pseudotuberculosis–induced infections that may difficult the diagnosis. Multiplex PCR revealed a valuable assay to detect C. pseudotuberculosis, in addition to routine methods applied to CL-diagnosis. No mycobacteria were identified in lymph nodes sampled, with and without apparent lesions. Nonetheless, due to public health impacts, this pathogen should be considered as a differential diagnosis of C. pseudotuberculosis–induced infections during inspection procedures of slaughtered sheep intended for human consumption.
Keywords: Corynebacterium spp; Multiplex PCR; Ovine lymphadenitis; Slaughterhouses